A decisão racional dos governantes pelos (des)cumprimento das soluções no âmbito da Comissão Interamericana de Direitos Humanos em face dos custos presumidos de implementação - Costa, Adriano Sousa (2018)
This research was anchored in the categorization of public policy tools (based on the Inter-American NATO model), which comprised the recommendations and agreements contained in the Inter-American Commission on Human Rights (IACHR) case follow-up report, year 2017. Based on the assumption that the governors analyze the costs and benefits before implementing these tools, it was sought to investigate whether the total solutions compliance rate was linked to variables relevant to the present research, namely: the form of solution , the formal complexity of design, the form of state and the political regime degree of freedom. The aforementioned variables would function as informational shortcuts for the present research, in order to indicate the presumed costs of the governor (institutional, economic, political and legal costs). Finally, the first hypothesis tested relates to the relation between the solutions of less complex cases (in relation to the number of tools that compose the design) and whether they would be more fully compliant and whether the medium or high complexity ones would actually have increased chances of being partially fulfilled or even unfulfilled. Another hypothesis tested relates to the demand form of solution (friendly or meritorious), since it was assumed that a case amicably solved could have a greater propensity to comply. The third hypothesis concerned the greater or lesser propensity of federated / unitary countries for full compliance with the solutions. Finally, the last hypothesis referred to the hypothetical aptitude of the countries (categorized and divided in face of their freedom degree )to the total fulfillment of the solutions. In order to arrive at the desired conclusions, a multinomial logistic model was constructed, promoting the crossing of such data, which seemed apt to the arrival of conclusions about the relations existing between the aforementioned dependent variables investigated and the total compliance solution rate.